THE EFFICIENCY OF TEACHING WITH SIMULTANEOUS PROMPTING TECHNIQUE WHILE TEACHING AN AUTISTIC STUDENT TO SHOW THE INSTRUMENT MENTIONED - Jale DENİZ (Fırat University, 2019)
This research was used to examine the effectiveness of simultaneous prompting in teaching of target behavior to show the instrument mentioned. The teaching of the skill which is not aimed at during the education has also been mentioned. The presentation of this skill has been made, in accordance with the aim, by making the subject play the instrument which he showed. The research has been conducted with a seven-year-old autistic boy attending in